Kedudukan Peraturan Mahkamah Agung Nomor 13 Tahun 2016 Dalam Mengatasi Kendala Penanggulangan Tindak Pidana Korporasi (The Role Of Regulation Of The Supreme Court Number 13 Year 2016 In Overcoming Obstacles Of Corporate Criminal Infringement) - Budi Suhariyanto (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2018)
The prevention of corporate crime in Indonesia is constrained due to unclear management of corporate crime. In order to overcome the imperfection of such arrangements, the Supreme Court issued Supreme Court Regulation No.13 of 2016 on the Procedures for Corruption Case Handling by Corporations. There are questions that arise, what are the obstacles faced by Law Enforcement in an effort to overcome corporate crime and how the role of Perma No. 13 of 2016 in overcoming the obstacles to overcome the criminal act of the corporation? Normative legal research method is used to answer the problem. Normatively, from various laws governing the corruption of the subject of crime, there is no detailed formulation of corporate handling procedures so that law enforcers experience difficulties in conducting the criminal proceedings against the corporation. Article 79 of the Law on the Supreme Court provides the legal basis that if there is a legal deficiency in the course of the judiciary in any case, the Supreme Court has the authority to enact legislation to fill such shortcomings or vacancies. Perma No.13 of 2016 can be used as a guide for Law Enforcement to overcome technical obstacles of corporation criminal procedure law. Nevertheless, Perma has limitation so that required update of corporation criminal procedure in RKUHAP. AbstrakPenanggulangan tindak pidana korporasi di Indonesia mengalami kendala akibat tidak jelasnya pengaturan penanganan tindak pidana korporasi. Dalam rangka mengatasi ketidaksempurnaan pengaturan tersebut, Mahkamah Agung menerbitkan Peraturan Mahkamah Agung No.13 Tahun 2016 tentang Tata Cara Penanganan Perkara Tindak Pidana Oleh Korporasi. Ada pertanyaan yang mengemuka yaitu apa saja kendala yang dihadapi Penegak Hukum dalam upaya menanggulangi tindak pidana korporasi dan bagaimana peran Perma Nomor 13 Tahun 2016 dalam mengatasi kendala penanggulangan tindak pidana korporasi tersebut? Metode penelitian hukum normatif digunakan untuk menjawab permasalahan tersebut. Secara normatif, dari berbagai peraturan perundang-undangan yang mengatur korporasi subjek tindak pidana, tidak dirumuskan detail tata cara penanganan korporasi sehingga penegak hukum mengalami kendala dalam melakukan proses pemidanaan terhadap korporasi. Pasal 79 Undang-Undang tentang Mahkamah Agung memberikan dasar hukum bahwa apabila dalam jalannya peradilan terdapat kekurangan atau kekosongan hukum dalam suatu hal, Mahkamah Agung memiliki wewenang membuat peraturan untuk mengisi kekurangan atau kekosongan tersebut. Perma No. 13 Tahun 2016 dapat dijadikan pedoman bagi Penegak Hukum untuk mengatasi kendala teknis hukum acara pidana korporasi. Namun, Perma tersebut memiliki keterbatasan sehingga diperlukan pembaruan hukum acara pidana korporasi dalam RKUHAP.